Fiscal Dynamics and Revenue Efficiency in South Indian States - Anjum M. (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
The study examines the fiscal performance and revenue efficiency of five South Indian states such as, Andhra Pradesh, Karnataka, Kerala, Tamil Nadu, and Telangana for the period 2011-12 to 2022-23, employing revenue performance index formula provided by Morris and Alpine (1982). Using index analysis as a primary tool, it evaluates the efficiency of mobilizing own revenue sources within the broader federal framework. The analysis indicates that own-tax revenue collection in the South Indian states remained consistently progressive, while Own Non-Tax Revenue improved in the post 2016, despite significant inter-state variations. Among the five states, Telangana recorded the highest score in own source revenue across both sub-periods, followed by Kerala and Karnataka. Telangana consistently emerged as the frontrunner in own-tax revenue efficiency during 2016-23, reflecting its effectiveness in mobilizing tax revenue from internal sources. In terms of non-tax revenue, Telangana also demonstrated consistent growth from 2015 onwards, ranking second after Kerala. Meanwhile, Kerala has remained in lead in mobilizing non-tax revenue from 2016 to 2023. In contrast, Andhra Pradesh dominated both tax and non-tax revenue performance until 2014 but witnessed a sharp decline post-bifurcation, highlighting the adverse fiscal consequences of state reorganization. Karnataka exhibited a notable turnaround in own source revenue performance, performing well in own-tax revenue collection between 2014 and 2015, though with limited non-tax revenue in the first half of the period. However, it showed a marked improvement in non-tax revenue during 2020 to 2023, indicating renewed policy focus. In the meanwhile, Tamil Nadu and Kerala, despite recording notable improvements between 2014-19, struggled to sustain growth momentum in subsequent years. Overall, the findings reveal significant variations in fiscal strategies and outcomes across the five states, reflecting diverse structural and administrative approaches to revenue mobilization within the federal system.